Pharmacotherapy a pathophysiologic approach - DiPiro, Joseph T. (McGraw-Hill Medical, 2011)
"The most comprehensive, widely used, and evidence-based pharmacotherapy text available Hailed by Doody's Review Service as "one of the best in pharmacy" Pharmacotherapy: A Pathophysiologic Approach is unmatched in its ability to help students develop a mastery of evidence-based medicine for optimum patient outcomes. The eighth edition will feature the addition of SI units throughout and an increased number of global examples and clinical questions. Features Unparalleled guidance in the development of pharmaceutical care plans Full-color presentation Key Concepts in each chapter Critical Presentation boxes summarize common disease signs and symptoms Clinical Controversies boxes examin complicated issues you face when providing drug therapy NEW material added to the online learning center EXPANDED evidence-based recommendations EXPANDED coverage of timely issues such as palliative care and pain medicine Therapeutic recommendations in each disease-specific chapter"--Provided by publisher